Tightening of the ATP-binding sites induces the opening of P2X receptor channels - Jiang, Ruotian (Nature Publishing Group, 2012)
The opening of ligand-gated ion channels in response to agonist binding is a fundamental process in biology. In ATP-gated P2X receptors, little is known about the molecular events that couple ATP binding to channel opening. In this paper, we identify structural changes of the ATP site accompanying the P2X2 receptor activation by engineering extracellular zinc bridges at putative mobile regions as revealed by normal mode analysis. We provide evidence that tightening of the ATP sites shaped like open ‘jaws' induces opening of the P2X ion channel. We show that ATP binding favours jaw tightening, whereas binding of a competitive antagonist prevents gating induced by this movement. Our data reveal the inherent dynamic of the binding jaw, and provide new structural insights into the mechanism of P2X receptor activation.